Carbon Dioxide Adsorption On Eaf Steel Slag Derived Adsorbent - Kuak, Li Ming (Universiti Sains Malaysia, 2017)
The objectives of this study are to synthesis EAF steel slag derived adsorbent for CO2 adsorption, to identify the surface functional group of prepared adsorbent by Fourier transform infrared spectroscopy (FTIR) technique and to investigate the adsorption performance of prepared adsorbent by using different parameters, initial CO2 concentration, temperature, gas flow rate and adsorbent loading. The electric arc furnace (EAF) steel slag derived adsorbent (EAFSSAD) is prepared in two steps, NaOH activation and followed by hydrothermal treatment. The functional groups of the prepared adsorbents were characterized by FTIR. The adsorption of carbon dioxide was carried out in a fixed bed adsorption system with an online carbon dioxide analyzer to determine the concentration of carbon dioxide in the outlet gas. The effect of operating conditions such as initial CO2 concentration (10 % - 20 %), adsorption temperature (30 °C -50 °C), gas flow rate (30 ml/min -70 mL/min) and adsorbent loading (1 g to 3 g) were studied. The highest bed adsorption capacity of EAFSSAD in this study is 72.41 mg/g with operating condition of 30 ml/min gas flow rate, 30 oC adsorption temperature, 10% initial CO2 concentration and 1.0g adsorbent loading. In a conclusion, the suitable operating condition for adsorption of CO2 on EAFSSAD is high initial CO2 concentration, low gas flow rate, low adsorption temperature and low adsorbent loading.